Two new species of Exidia sensu lato (Auriculariales, Basidiomycota) based on morphology and DNA sequences - Tohtirjap, Ablat; Hou, Shi-Xing; Rivoire, Bernard; Gates, Genevieve; Wu, Fang; Dai, Yu-Cheng (Frontiers in Microbiology, 2023)
Fourteen Exidia-like specimens were collected from China, France and Australia and were identified as four species in Exidia sensu lato, including Exidia saccharina, Tremellochaete atlantica and two new species (E. subsaccharina and T. australiensis), based on morphological characteristics and phylogenetic analyses using the internal transcribed spacer regions (ITS), and the large subunit of nuclear ribosomal RNA gene (nLSU) in the present study. The four species are described and illustrated in detail. Two known species, E. saccharina and T. atlantica are reported from China for the first time. Two new species, E. subsaccharina and T. australiensis are described from France and Australia, respectively. Exidia subsaccharina is characterized by its reddish brown to vinaceous brown basidiomata, slightly papillate hymenial surface, and narrowly allantoid basidiospores usually without oil drop measuring 12.5–17.5 × 4.2–5.5 µm, and differs from the similar species, E. saccharina, by distinctly larger basidiospores (12.5–17.5 × 4.2–5.5 µm vs. 10–14.2 × 3.2–4.5 µm). Tremellochaete australiensis is characterized by its white to greyish blue basidiomata, obviously and densely papillate hymenial surface, and allantoid basidiospores usually with oil drop measuring 13.8–16.2 × 4.8–6.5 µm, and also can be distinguished from the similar species, T. atlantica and T. japonica, by its distinctly larger basidiospores (13.5–17.8 × 4–5.2 µm vs. 10–11.8 × 4–4.8 µm in T. atlantica; 9.4–11.8 × 3.5–4.2 µm in T. japonica).